Bipolar as a Creative Idea for the Creation of Nodus Tollens Dance Works - Revilma Shintia; Venny Rosalina (CV. AFDIFAL MAJU BERKAH, 2023)
Nodus Tollens’ is the title of a dance art work that uses the psychological approach of Bipolar Disorder. The choreography of the work is composed to express the idea of Bipolar that affects one's mindset and emotions. Nodus Tollens' work is a picture of the behavior, habits, and character of humans with bipolar who are transferred into gestures using contemporary dance techniques. This study describes the process of choreographing creation and exploration of the Bipolar body with three episodes of depression, manic and hypomanic. Nodus Tollens' work became a performance with a creative process that prioritized the science of dance choreography. Some of the things presented in Nodus Tollens' dance work include the social value of society in interpreting bipolar sufferers. This research uses a qualitative approach with an orientation of meaning and understanding.